A concise history of Chinese philosophy - Feng, Qi 1915-1995; Chen, Weiping 1951- (Springer, 2023)
This book is an abridged version of Feng Qi's two major works on the history of philosophy, The Logical Development of Ancient Chinese Philosophy and The Revolutionary Course of Modern Chinese Philosophy. It is a comprehensive history of Chinese philosophy taking the reader from ancient times to the year 1949. It illuminates the characteristics of traditional Chinese philosophy from the broader vantage point of epistemology. The book revolves around important debates including those on "Heaven and humankind" (tian ren ), "names and actualities" (mingshi ), "principle and vital force" (liqi ), "the Way and visible things" (daoqi ), "mind and matter/things" (xinwu ), and "knowledge and action" (zhixing ). Through discussion of these debates, the course of Chinese philosophy unfolds. Modern Chinese philosophy has made landmark achievements in the development of historical and epistemological theory, namely the "dynamic and revolutionary theory of reflection". However, modern Chinese philosophy is yet to construct a systematic overview of logic and methodology, as well as questions of human freedom and ideals. Amid this discussion, the question of how contemporary China is to "take the baton" from the thinkers of the modern philosophical revolution is addressed.-
Keywords: Ideengeschichte; Philosophie; China; Oriental & Indian philosophy; Ostasiatische und indische Philosophie; PHILOSOPHY / Eastern